1967
DOI: 10.1063/1.1840465
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of Hexaquo Metal Ions. I. Chromium (III)

Abstract: The optical spectra of the hexaquochromium (III) ion in the host crystals of C(NH2)3Al(SO4)2·6 H2O and several isomorphs, and in AlCl3·6 H2O, are presented and discussed. The broad-band spectra have been analyzed to determine trigonal field parameters, and these results are confirmed by the analysis of the fine-line spectra. The off-diagonal element of the trigonal field, v′, is shown to be as large in magnitude as v, and therefore to be of considerable importance in the interpretation of polarized spectra. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1968
1968
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In the present work, the ratio of 10 D q /B is 26.5. The reported value of 10 D q /B for hexaquochromium is 27.5 [29]. This suggests that in the present system [CrMTH], the transition metal ion is surrounded by six water molecules.…”
Section: Article In Pressmentioning
confidence: 83%
“…In the present work, the ratio of 10 D q /B is 26.5. The reported value of 10 D q /B for hexaquochromium is 27.5 [29]. This suggests that in the present system [CrMTH], the transition metal ion is surrounded by six water molecules.…”
Section: Article In Pressmentioning
confidence: 83%
“…The rejection of the two-site interpretation and the assignment of the 14 109 and 14 092 cm-1 lines to the components of 2E 4-4Az was made on the basis of a simple axial ligand field model (1). In this model the 4T2 splitting, as measured by the separation of the band maxima of 4Al(4T2)4-4AT and 4E(4T2) 4-4AK, and the 2E splitting are both proportional to the same trigonal field parameter, v (6).…”
Section: Discussion R Lines In Gashmentioning
confidence: 99%
“…The ZE*-4A2 absorption spectra of hexaquochromium (III) ions in the crystalline hosts C(NHZ),Al(S04)2• 6HZO(GASH) and AlC13• 6HTO have been described in some detail (1,2)• The two strong absorption lines in the pure . GCrSH spectrum were assigned to the split components of ZE *_4A2 (R lines), inconflict with the interpretation of Martin-Bruneti re and Couture wherein these lines were ascribed to the unsplit TE *-4Az…”
Section: Introductionmentioning
confidence: 99%
“…The average covalence factor N can be determined by corresponding optical spectra at different temperatures. For GASH:Cr 3+ and AlCl 3 · 6H 2 O:Cr 3+ systems, the optical spectra at 4.2 K have not been reported so far, so it is reasonable to approximately apply the optical spectra at 20 K to the calculation since the optical spectra have a decreasing tendency in the temperature range 27. In this case we obtain N = 0.936 (4.2 K), 0.929 (77 K), 0.928 (195 K), 0.926 (297 K) for the GASH:Cr 3+ system and N = 0.925 (4.2 K), 0.923 (77 K), 0.926 (195 K), 0.922 (297 K) for the AlCl 3 · 6H 2 O:Cr 3+ system, which will be fixed in the following calculation.…”
Section: Calculation For [Cr(h2o)6]3+ Complex In Gash:cr3+ and Alclmentioning
confidence: 99%
“…Usually, the properties of materials depend strongly upon the microscopic structure around impurity center, which can be investigated by means of electron paramagnetic resonance (EPR) and optical spectra techniques. A lot of experimental EPR and optical spectra of transition‐metal ions in GASH and AlCl 3 · 6H 2 O, especially Cr 3+ , have been reported 20–27. Among them, Manoogian and Leclerc 24 have measured the temperature dependence of the zero‐field splitting (ZFS) parameter D , and found that GASH:Cr 3+ and AlCl 3 · 6H 2 O:Cr 3+ systems have a common feature, that is, the ZFS parameter D is negative and its magnitude increases with decreasing temperature.…”
Section: Introductionmentioning
confidence: 99%